A biblical, cultural and missiological critique of traditional circumcision among Xhosa-speaking Christians - J. Papu; P. Verster (Acta Theologica)
Among the Xhosa of South Africa, male circumcision remains a very important ritual. The question as to whether Christians should accept these rites and continue to send their children to traditional schools practising it is very important. In this article the implications of the ritual and the way in which proponents use the Bible are evaluated. It is argued that there should be an honest encounter with the rite from a biblical perspective. Solutions should be evaluated and explained. From a Christian perspective total rejection is not possible, but the church should remain faithful to the truth of the gospel.